2009
DOI: 10.1017/s0030605307002311
|View full text |Cite
|
Sign up to set email alerts
|

Subterranean herpetofauna show a decline after 34 years in Ndumu Game Reserve, South Africa

Abstract: Subterranean herpetofauna comprise an estimated 20% of the world's amphibians and reptiles but are one of the least studied groups of terrestrial vertebrates. Monitoring population trends and threats to these species is dependent in part on quantitative historical data, which are generally lacking. One exception is a 1970 study conducted in Ndumu Game Reserve, South Africa. We revisited this area in 2004 and carried out comparative quantitative sampling in deciduous broad-leaf woodland and sand forest habitats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…Individuals are normally only encountered when large quantities of soil are moved, or when areas become flooded in extreme weather events. Few techniques have been proposed for their sampling, although Measey (2006) and Measey et al (2009) suggested digging quadrats for quantitative sampling of Zygaspis vandami. Branch ( 2006) called for the phylogenetic resolution of this group as a priority (but see Measey and Tolley, 2013) and taxonomic work at species level is ongoing.…”
Section: Subterranean Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals are normally only encountered when large quantities of soil are moved, or when areas become flooded in extreme weather events. Few techniques have been proposed for their sampling, although Measey (2006) and Measey et al (2009) suggested digging quadrats for quantitative sampling of Zygaspis vandami. Branch ( 2006) called for the phylogenetic resolution of this group as a priority (but see Measey and Tolley, 2013) and taxonomic work at species level is ongoing.…”
Section: Subterranean Vertebratesmentioning
confidence: 99%
“…Some species are known to occur at substantial depths in the soil profile and are known to be able to generate considerable burrowing forces (Navas et al, 2004). Pooley et al (1973) reported surprisingly high densities, but Measey et al (2009) failed to find comparable densities in the same areas 35 years later, prompting concerns about their current conservation status. The conservation status of amphisbaenians is largely unknown, with 50% of species being classified as Data Deficient (Böhm et al, 2013).…”
Section: Subterranean Vertebratesmentioning
confidence: 99%
“…Soil biodiversity is considered to be an important factor in regulating the functioning of terrestrial ecosystems, but this importance is often not appreciated (Decaens et al, 2006), and the absence of concern about fossorial animals from conservationists is conspicuous (Wolters, 2001;B€ ohm et al, 2013). This may have unfortunate consequences for conservation planning, because fossorial species may be at particular risk from anthropogenic disturbance and local extinction of fossorial populations due to landscape and soil alterations may be occurring unnoticed (How and Shine, 1999;McKenzie et al, 2003;Zeppel et al, 2003;Measey, 2006;Measey et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While the threat status of other tetrapods (mammals, birds and amphibians) have been reviewed at a global scale based on full species sampling [8] – [10] , reptiles (with the exception of turtles and crocodilians) have traditionally received much less attention from conservationists (but see [11] ). This is particularly the case for cryptic, rare and burrowing species that are difficult to sample (e.g., [12] , [13] ). Many species of reptiles have small geographic ranges (e.g., [14] ) and have developed special ecological adaptations and dependency on specific habitats and environmental conditions [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%